The Value of Bank Durability: Borrowers as Bank Stakeholders. - Polonchek, John A; Slovin, Myron B; Sushka, Marie E (Journal of Finance, 1993)
The authors examine the value of bank durability to borrowing firms. The analysis is based on theoretical models of the asset services view of intermediation that imply that private information and associated relationship-specific activities are intrinsic to bank lending. The authors analyze share price effects on firms with lending relationships with Continental Illinois Bank during its de facto failure and subsequent FDIC rescue. They find the bank's impending insolvency had negative effects and the FDIC rescue positi ve effects on client firm share prices. The authors conclude that borro wers incur significant costs in response to unanticipated reductions in bank durability and, thus, are bank stakeholders.